Description of the learning results of 3 vulnerable schools with management based on the distributed leadership model, Santiago, Chile. - Fre Salas, Victor; Muñoz Sánchez, Segundo; Virán López, Ana Karina; Schmitt Bernal, Eliana (PEM. Revista de Didáctica, Evaluación e Innovación, 2024)
ABSTRACT.Considering the diverse needs in educational research in the current context, and acknowledging that achieving a perfect educational system is not feasible, the challenge lies in striving for continuous improvement where quality is the primary goal. In this scenario, reflections on leadership have much to contribute.A review of the literature on the topic of leadership has demonstrated that the chosen model within the educational community is crucial. For this reason, the proposal of Distributed Leadership offers significant contributions when analyzing learning outcomes, particularly in contexts with high levels of educational vulnerability.